1996
DOI: 10.1128/aem.62.7.2387-2392.1996
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the biodegradation of phenanthrene by Pseudomonas stutzeri P16 in the presence of a nonionic surfactant

Abstract: The low water solubility of polycyclic aromatic hydrocarbons is believed to limit their availability to microorganisms, which is a potential problem for bioremediation of polycyclic aromatic hydrocarbon-contaminated sites. Surfactants have been suggested to enhance the bioavailability of hydrophobic compounds, but both negative and positive effects of surfactants on biodegradation have been reported in the literature. Earlier, we presented mechanistic models of the effects of surfactants on phenanthrene dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(56 citation statements)
references
References 34 publications
(58 reference statements)
1
53
2
Order By: Relevance
“…As illustrated in Figure 1A, the SMWT site soil microbes were able to degrade the water-dissolved PHE present in surfactant-and soil-free bioreactors without adaptation period (the first-order rate coefficient, k ϭ 0.559/d). Although our PHE removal rate was lower than those reported in prior laboratoryscale PHE biodegradation studies [3][4][5] because of the relatively low biomass inoculated in this study, it is evident that the mixed microbial consortia eluted from the SMWT site soil and then harvested in LB medium exhibited PHE-degrading activity. Essentially constant PHE concentrations were observed in a parallel abiotic control reactor, indicating neither PHE biodegradation nor its sorption by biomass.…”
Section: Behavior Of Phe and Tween 80 In Soil-free Bioreactor Systemscontrasting
confidence: 88%
See 1 more Smart Citation
“…As illustrated in Figure 1A, the SMWT site soil microbes were able to degrade the water-dissolved PHE present in surfactant-and soil-free bioreactors without adaptation period (the first-order rate coefficient, k ϭ 0.559/d). Although our PHE removal rate was lower than those reported in prior laboratoryscale PHE biodegradation studies [3][4][5] because of the relatively low biomass inoculated in this study, it is evident that the mixed microbial consortia eluted from the SMWT site soil and then harvested in LB medium exhibited PHE-degrading activity. Essentially constant PHE concentrations were observed in a parallel abiotic control reactor, indicating neither PHE biodegradation nor its sorption by biomass.…”
Section: Behavior Of Phe and Tween 80 In Soil-free Bioreactor Systemscontrasting
confidence: 88%
“…Those are, first, inhibition due to high surfactant concentration, second, preferential surfactant utilization by microbes including PAH degraders, and third, toxic or inhibitory intermediates or dead-end compounds produced from surfactant biodegradation, if the second potential factor were possible. However, a number of prior studies demonstrated that PAH biodegradation was not inhibited even at very high surfactant concentrations ranging from 150 to 1,000 ϫ CMC of nonionic surfactants used [4,5,21,23]. Slow PHE biodegradation observed after 19 d of incubation in our study also supports that microbial activity was not completely repressed in the range of initial Tween 80 concentrations tested (200-1,000 mg/L), which may rule out the first potential factor and also suggests that this inhibition may have been temporal, in other words, a reversible inhibitory effect [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Triton X-100 significantly inhibited metabolite production by B8/36 for both PAHs, indicating that significant enhancement of the PAH oxidation rate may be facilitated by nontoxic surfactant enhancement (HMN) where the rate of PAH biodegradation is otherwise limited by mass transfer. The contrasting effects of the nonionic surfactant on the biotransformation of PAHs by the two bacteria in this study may explain why previous studies on the application of surfactants to PAH bioremediation have yielded inconclusive results [58,75]. Pinto and Moore [76] determined the extent to which fourand five-ring PAHs could be released from different soil types by the nonionic surfactant Tween 80 (Sigma, St. Louis, MO, USA) and whether microorganisms could oxidize the surfactant-solubilized PAHs present in soil washings.…”
Section: Surfactant Enhancements For Bioavailabilitymentioning
confidence: 85%
“…Pseudomonas putida has been extensively studied in environmental biotechnology because of its capabilities in the bioremediation of toxic organic wastes including aromatic hydrocarbon compounds (Loh & Cao, 2008). Other Pseudomonas species identified with bioremediation properties include P. mendocina (Whited & Gibson, 1991) and P. stutzeri (Grimberg, 1996).…”
Section: Plant Growth Promotion and Bioremediationmentioning
confidence: 99%